Addressing Health Equity Through Action on the Social Determinants of Health: A Global Review of Policy Outcome Evaluation Methods - Janice Lee; Ashley Schram; Emily Riley; Patrick Harris; Fran Baum; Matt Fisher; Toby Freeman; Sharon Friel (Kerman University of Medical Sciences, 2018)
Background Epidemiological evidence on the social determinants of health inequity is well-advanced, but considerably less attention has been given to evaluating the impact of public policies addressing those social determinants. Methodological challenges to produce evidence on policy outcomes present a significant barrier to mobilising policy actions for health equities. This review aims to examine methodological approaches to policy evaluation of health equity outcomes and identify promising approaches for future research. Methods We conducted a systematic narrative review of literature critically evaluating policy impact on health equity, synthesizing information on the methodological approaches used. We searched and screened records from five electronic databases, using pre-defined protocols resulting in a total of 50 studies included for review. We coded the studies according to (1) type of policy analysed; (2) research design; (3) analytical techniques; (4) health outcomes; and (5) equity dimensions evaluated. Results We found a growing number of a wide range of policies being evaluated for health equity outcomes using a variety of research designs. The majority of studies employed an observational research design, most of which were cross-sectional, however, other approaches included experimental designs, simulation modelling, and meta-analysis. Regression techniques dominated the analytical approaches, although a number of novel techniques were used which may offer advantages over traditional regression analysis for the study of distributional impacts of policy. Few studies made intra-national or cross-national comparisons or collected primary data. Despite longstanding challenges of attribution in policy outcome evaluation, the majority of the studies attributed change in physical or mental health outcomes to the policy being evaluated. Conclusion Our review provides an overview of methodological approaches to health equity policy outcome evaluation, demonstrating what is most commonplace and opportunities from novel approaches. We found the number of studies evaluating the impacts of public policies on health equity are on the rise, but this area of policy evaluation still requires more attention given growing inequities